Low Risk of Recurrence After Posterior Labral Repair of the Shoulder in a High-Risk United States Military Population - Stephen Chan, M.D; Lisa K. O'Brien, D.O; Brian R. Waterman, M.D; Andrew G. Chan, M.D., M.P.H; Mark Pallis, D.O; Kelly G. Kilcoyne, M.D (Elsevier, 2020)
Purpose: To examine the results of isolated arthroscopic posterior labral repair of the shoulder in an active military population, looking specifically at the reoperation rate and rate of return to previous military activity with a minimum follow-up period of 2 years. Methods: A retrospective case series was performed in active-duty military service members who underwent isolated, primary arthroscopic posterior labral repair at a single academic military treatment facility between 2009 and 2015 and had at least 2 years of follow-up. Patients were excluded if they were of non-active-duty status, had insufficient follow-up (<2 years), or had undergone a concurrent procedure. Injury presentation, demographic data, and surgical data (i.e., surgical positioning, number of anchors, and anchor placement location) were compiled manually. Outcomes including the rate of return to active duty, recurrence of symptoms, and need for revision surgery were evaluated. Results: Sixty-five patients were included. After arthroscopic repair, a high rate of return to previous military duties (83%) was noted at short- to mid-term follow-up (mean ± standard deviation, 3.04 ± 1.30 years), with 1 patient (1.5%) requiring revision arthroscopic repair and 10 patients (15.5%) showing activity-limiting shoulder pain preventing a return to active duty. Intraoperative positioning (P = .17), a low anchor position (P = .27), and the number of anchors used (P = .62) were not found to be significant contributors to continued postoperative pain or recurrent instability. Conclusions: Arthroscopic intervention resulted in a reliable rate of glenohumeral stability with a low rate of surgical revision and a high rate of return to military duty at short- to mid-term follow-up. However, 1 in 6 military service members showed significant, activity-limiting shoulder pain postoperatively that did not permit a return to previous military activities after surgical intervention. Level of Evidence: Level IV, therapeutic case series.